2018
DOI: 10.1126/scisignal.aau0597
|View full text |Cite
|
Sign up to set email alerts
|

Substrate binding allosterically relieves autoinhibition of the pseudokinase TRIB1

Abstract: The Tribbles family of pseudokinases recruits substrates to the ubiquitin ligase COP1 to facilitate ubiquitylation. CCAAT/enhancer-binding protein (C/EBP) family transcription factors are crucial Tribbles substrates in adipocyte and myeloid cell development. We found that the TRIB1 pseudokinase was able to recruit various C/EBP family members and that the binding of C/EBPβ was attenuated by phosphorylation. To explain the mechanism of C/EBP recruitment, we solved the crystal structure of TRIB1 in complex with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 62 publications
4
83
0
Order By: Relevance
“…C Quantification of the average ratio of nuclear/cytoplasmic fluorescence of GFP-COP1 constructs in (A) and (B). Alternatively, a conformational change in the TRIB1 pseudokinase domain induced by C/EBPa binding (Jamieson et al, 2018) could alter the ability of TRIB1 to form interactions necessary for its localization to PML bodies. are shown for three independent experiments where 50 individual cells per experiment were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…C Quantification of the average ratio of nuclear/cytoplasmic fluorescence of GFP-COP1 constructs in (A) and (B). Alternatively, a conformational change in the TRIB1 pseudokinase domain induced by C/EBPa binding (Jamieson et al, 2018) could alter the ability of TRIB1 to form interactions necessary for its localization to PML bodies. are shown for three independent experiments where 50 individual cells per experiment were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that mutations in the pseudokinase domain affect interactions between Tribbles and its binding partners. Recently, a crystal structure of TRIB1 in complex with a C/EBPa peptide revealed the binding site for C/EBPa within the C-lobe of the TRIB1 pseudokinase domain (Jamieson et al, 2018). A mutation within the HRD motif in the Drosophila Tribbles homolog ablates its interactions with Akt and the C/EBP homolog Slbo (Masoner et al, 2013;Das et al, 2014).…”
Section: Trib1 Promotes Nuclear Accumulation Of Cop1mentioning
confidence: 99%
See 3 more Smart Citations